2014
DOI: 10.1016/j.snb.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of carbon nanotubes on a nanoporous gold electrode for acetylcholinesterase biosensor design

Abstract: a b s t r a c tAn electrochemical sensing platform based on assembly of carbon nanotubes on a nanoporous gold electrode is described for highly sensitive detection of organophosphate pesticides. The nanoporous gold film (NPG) electrode is fabricated by an alloying/dealloying process, which possess high electroactive surface area and is an excellent substrate for sensor design. The NPG functionalized with cysteamine allows the immobilization of carbon nanotubes on the electrode with the self-assembly technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 46 publications
(54 reference statements)
0
16
0
1
Order By: Relevance
“…Organophosphate pesticides (OPs) play an important role in increasing agricultural productivity due to their high insecticidal activity [1][2][3]. Unfortunately, owing to their high acute toxicity and bioaccumulation effect, the residue in the environment can cause long-term damage to human health [4].…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphate pesticides (OPs) play an important role in increasing agricultural productivity due to their high insecticidal activity [1][2][3]. Unfortunately, owing to their high acute toxicity and bioaccumulation effect, the residue in the environment can cause long-term damage to human health [4].…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanocomposites allows for detecting the inhibitors at very low detection limit, but very often requires high potential, even higher than the sensor modified with only carbon nanotubes. The CNTs were also used as a link between the cysteamine immobilised onto nanoporous gold film electrode and AChE (Ding et al, 2014). As expected, the detection of substrate occurred at a high potential (the peak of thiocholine oxidation was observed at at 913 mV in cyclic voltammetry), however the developed biosensor leads to detect the malathion with a detection limit of 0.5 ppb.…”
Section: Carbon Nanomaterialsmentioning
confidence: 65%
“…Another possibility to reduce the applied potential is the using of novel materials such as carbon nanotubes [50][51][52][53][54][55][56] . Carbon nanotubes exhibit electrocatalytic activity toward thiocholine and possess high surface area.…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…Chauhan and Pundir immobilized AChE via covalent binding on Fe 3 O 4 nanoparticle/multi-walled carbon nanotube-modified indium tin oxide-coated glass plate for detection of malathion, chlorpyrifos, monocrotophos and endosulfan 52 . Ding et al designed an electrochemical sensing platform based on assembly of carbon nanotubes on a nanoporous gold electrode for sensitive detection of pesticides 50 . Kesik et al reported an amperometric biosensor based on a conducting polymer using multi-walled carbon nanotubes for detection of organophosphates.…”
Section: Nanomaterialsmentioning
confidence: 99%